Pengaruh Persepsi Profesi Perpajakan, Pengetahuan Pajak, dan Penghargaan Finansial terhadap Minat Berkarir di bidang Perpajakan - Rifaldo Ghufron; Herawansyah (Jurnal Informatika Ekonomi Bisnis, 2023)
This research was conducted to examine the influence of perceptions of the tax profession, knowledge of taxation, and financial rewards on interest in a career in the field of taxation. The research adopts a quantitative approach, with data obtained through the distribution of questionnaires via Google Forms. The population for this study comprised accounting students at Bengkulu University, and the research sample was determined using purposive sampling. Throughout the research period, data was collected from 71 respondents. The gathered data were processed using the SPSS 24 application with the multiple linear regression method. The findings of this research indicate that perceptions of the tax profession positively influence interest in a career in the field of taxation. However, tax knowledge and financial rewards do not exhibit any influence on interest in a career in taxation.